Abdominal pain patient referrals to emergency surgical service : appropriateness of diagnosis and attitudes of general practitioners - Kozomara, Davorin (Array, 2009)
Abstract: This study evaluate the need for general practitioners referrals and self referrals of acute abdominal pain patients to emergency surgical service, the appropriateness of GP referral diagnosis and their attitudes dealing with abdominal pain. In three months period all acute abdominal pain patient referrals to our hospital emergency surgical service were audited. Data on final diagnosis, surgical treatment, admission to hospital and surgery performance were recorded. Self referral or GP referral, referring GP diagnosis, referral letters indicating presenting complaint or history, axillar and rectal temperature measurement, laboratory checking and abdominal radiography checking by GP were recorded as well. Also, GPs examination details as palpation, auscultation and digit-rectal checking were recorded. We calculated sensitivity, specificity, positive and negative predictive value (PV) for referring diagnosis. Self referrals and GP referrals differences were evaluated.